Movement Navigator: A Relational Syntax Study on Movement and Space at King’s Cross and Piccadilly Circus Underground Stations, London, UK - Suvanajata, Rapit (Journal of Architectural/Planning Research and Studies (JARS), 2005)
The article explores the design and analytical method Relational Syntax [1], using both a syntactical approach as well as on-site observations. The architecture of King’s Cross and Piccadilly Circus Underground stations in London is used as the laboratory in which a theoretical discussion on movement and dimensional relations in architectural space is conducted. The two stations are among the most well-known and used in the London Underground system. Observations were made at these highly-used stations in order to establish an overall understanding of the spatial mechanism through social and natural movement. Considering the case studies as both texts and experiences, the article shows that spatial analysis and bodily movement can be explained, compared and put into sets of relations that can be pre-established or scripted during architects’ design activities. It is argued that the concept of ‘script’ [2] can be used bi-directionally in both the design and analysis of architecture. The research and arguments presented in this paper are being developed to form the basis of an application tool. Based on the theory of Relational Syntax, this application tool can be used to process building requirements generated from the design or analysis of a piece of architecture into scripts in order to systematically and aesthetically describe and generate spatial relations in buildings.